Financial feasibility analysis of beef cattle fattening business in Balikpapan City - Annisa Puteri, Sarah Shevi; Mayulu, Hamdi; Tricahyadinata, Irsan; Christiyanto, Marry; Rorimpandey, Boyke (INOVASI: Jurnal Ekonomi, Keuangan, dan Manajemen, 2023)
The objective of this research was to determine the financial feasibility of the beef cattle fattening business in Balikpapan City.  The research was carried out by using a survey method in the North Balikpapan Sub-district of Balikpapan City. The respondents were determined based on purposive sampling and 40 respondents by considering the beef cattle ownership which has at least two heads of beef cattle with more than a one-year rearing period. Financial feasibility analysis used Break Event Point (BEP), Net Present Value (NPV), Benefit Cost Ratio (B/C Ratio), Internal Rate of Return (IRR), and Payback Period (PP). Based on the calculation, the BEP was IDR9.676.911; NPV(9.15%): IDR 1.017.779.514; NPV(14.15%): IDR952.403.118; B/C Ratio 2.7; IRR 87% and PP 0.37 year. According to the results, it could be concluded that the beef cattle business in the North Balikpapan Sub-district, Balikpapan City was feasible